THE EFFECT OF OPTIMIZATION OF THE COAL PRODUCTION VALUE OF PT TAMBANG BATUBARA BUKIT ASAM (PTBA) AT MUARA ENIM REGENCY ON NET SOCIAL GAIN OF THE LOCAL COMMUNITY TO FULFILL THE NATIONAL COAL DEMAND - (NIM: 22107010); Pembimbing : Dr.-Ing. Ir. Aryo P. Wibowo, M.Eng; Dr. Ir. H. Ukar W. Soelistijo, TONI
Since coal is a part of national mineral resources, the exploitation of coal has to achieve the Indonesian society welfare at the utmost (1945 Constitution, article 33, verse 3). Moreover, it is necessary to enhance an optimization of coal value related to national security of supply. At regional scope of Kabupaten Muara Enim, this tesis will examine the effect of optimization of coal production value per capita income using the models of input-output (I-O) combined with linier programming (LP), the net social gain (NSG), net gain coeficient (NGC), and Pareto optimization. The optimization shows that during the year of 1997-2008 the average value of PTBA coal production, YSBB KME, is about IDR 3,089,601 Millions, or it is a 17% increase of actual coal value, YSBB KME of IDR 2,632,702 Millions. At the same periode, the average of actual NSG is IDR 188,902 Millions. The NSG grows about 24.7% per year with NGC of 0.0394 it means that if the output of coal raise by IDR 1,000, then the NSG will increase by IDR 39.4 or 3.94% of the output.